Ecological drivers shaping mainstem and tributary fish communities in the upper Jinsha River, southeastern Qinghai-Tibet Plateau - Pengcheng Lin; Masami Fujiwara; Baoshan Ma; Zhijun Xia; Xinghua Wu; Chunling Wang; Tao Chang; Xin Gao (Ecological Processes)
Abstract Background Elucidating spatial variation in ecological communities and the mechanisms of community assembly is crucial for biodiversity conservation in river ecosystems. The upper Jinsha River located in the eastern part of the Qinghai-Tibet Plateau, is experiencing intensified human activities, such as hydropower development. In this study, fish surveys were conducted at 38 sites, including 15 mainstem sites and 23 tributary sites of the upper Jinsha River, China, to analyze the spatial patterns and ecological drivers of fish communities. Results NMDS and PERMANOVA analysis revealed significant disparities in the fish communities between the mainstem and tributaries. Schizothorax dolichonema and Schizopygopsis malacanthus dominated the mainstem, whereas Schizopygopsis malacanthus, Schizothorax wangchiachii, and Triplophysa stenura dominated the tributaries. Fish beta diversity exhibited substantial turnover across the mainstem, tributaries, and entire river basin. Both environmental factors (e.g., altitude and the proportion of cobble substrate) and spatial variables were significantly correlated with fish beta diversity, but their relative importance differed between the mainstem and tributaries. Specifically, in the mainstem, environmental variables emerged as the primary drivers. In contrast, spatial factors assumed a predominant role in the tributary communities. Conclusions The results suggested that environmental filtering predominantly drove fish community assembly in the mainstem, whereas dispersal limitation exerted had a greater influence on the fish communities in the tributaries. These results contribute to our understanding of the spatial patterns and formation mechanisms of fish assemblages between mainstem and tributaries in high-altitude rivers, such as the upper Jinsha River. In the context of hydropower development in the upper Jinsha River, our findings offer insights into the management and conservation of fish diversity.